Parasites of Arctic char (Salvelinus alpinus) in North America: a systematic literature review and an analysis of contemporary data from anadromous populations from Nunavut - Les N. Harris; Phillip R. Morrison; Michael W. Johnson; Sara Bolduc; Ariane Côté; Amélie Papillon; Justine Lapointe; Xuehan Qu; David J. Yurkowski; Connor W. Faulkner; Colin P. Gallagher; Lauren N. Wiens; et al. (Reviews in Fish Biology and Fisheries, 2026)
Parasites play a critical yet understudied role in Arctic ecosystems, particularly within key subsistence species such as Arctic char ( Salvelinus alpinus ). As the Arctic undergoes rapid climate-driven change, establishing baseline parasite biodiversity is essential for monitoring ecological shifts and anticipating emerging health and conservation concerns. This study provides the most comprehensive assessment to date of Arctic char parasites in the North American Arctic by integrating a systematic literature review with new empirical data from 378 Arctic char collected across five Nunavut areas (2020–2024). The literature review (30 studies, 1956–2024) documented 67 parasite taxa—48 identified to species—with helminths (nematodes, cestodes, trematodes, acanthocephalans) dominant. Overall, 82% of taxa occurred in anadromous Arctic char and 54% in freshwater forms, including 22 species unique to anadromous fish. Our empirical assessment identified 35 parasite taxa—23 to species level—including several previously unreported from Arctic char in this region. Common and widespread parasites documented in the empirical assessment included Brachyphallus crenatus , Derogenes varicus , Bothrimonus sturionis , and Alloopistholecithum gibbosum , although notable spatial variation occurred in community composition and infection intensity. The occurrence of rare and previously unreported parasites may suggest emerging shifts in host–parasite dynamics potentially linked to changing prey availability and northward species range expansions. Together, these findings establish an essential baseline for Arctic char parasite biodiversity and highlight the need for continued monitoring to track future changes driven by climate warming, shifting food webs, and their implications for fish health and food security in northern Indigenous communities.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Phytoremediation of an acid tar pit at Cinderhill, Derbyshire, UK: Lessons learned and future challenges - Matthew F. Johnson; Harvey Wood; Samantha Bryan; Sean Craig; Will Meredith; Colin Snape; Clement N. Uguna (Journal of Environmental Management, 2026)

Basaltic island evolution close to the limits of reef growth: Norfolk Island, Southwest Pacific - Alysha M. Johnson; Mark E. Dickson; Sarah M. Hamylton; Elizabeth Johnstone; Rafael C. Carvalho; Colin D. Woodroffe (Geomorphology, 2026)

From pixels to parcels: Flexible, practical small-area uncertainty estimation for spatial averages obtained from aboveground biomass maps - Lucas K. Johnson; Grant M. Domke; Stephen V. Stehman; Michael J. Mahoney; Colin M. Beier (Remote Sensing of Environment, 2025)

The role of MEGF10 in myoblast fusion and hypertrophic response to overload of skeletal muscle - Louise Richardson; Ruth Hughes; Colin A. Johnson; Stuart Egginton; Michelle Peckham (Journal of Muscle Research and Cell Motility, 2025)
Biallelic mutations in multiple EGF domain protein 10 ( MEGF10 ) gene cause EMARDD (early myopathy, areflexia, respiratory distress and dysphagia) in humans, a severe recessive myopathy, associated with reduced numbers of PAX7 positive satellite cells. To better understand the role of MEGF10 in satellite cells, we overexpressed human MEGF10 in mouse H-2k b -tsA58 myoblasts and found that it inhibited fusion. Addition of purified extracellular domains of human MEGF10, with (ECD) or without (EGF) the N-terminal EMI domain to H-2k b -tsA58 myoblasts, showed that the ECD was more effective at reducing myoblast adhesion and fusion by day 7 of differentiation, yet promoted adhesion of myoblasts to non-adhesive surfaces, highlighting the importance of the EMI domain in these behaviours. We additionally tested the role of Megf10 in vivo using transgenic mice with reduced ( Megf10 +/− ) or no ( Megf10 −/− ) Megf10. We found that the extensor digitorum longus muscle had fewer anti-Pax7 stained cell nuclei and was less able to undergo hypertrophy in response to muscle overload concomitant with a lower level of satellite cell activation. Taken together, our data suggest that MEGF10 may promote satellite cell adhesion and survival and prevent premature fusion helping to explain its role in EMARDD.

A Mutation in Damage-Specific DNA Binding Protein One (ddb-1) Underlies the Phenotype of the No-Marginal-Zone (nmz) Mutant Zebrafish - Kailey Jerome; Aria Gish; Taylor Aakre; Taylor Brend; Mara Kate Grenier; Christina L. Johnson; Jaxon Gronneberg; Colin K. O’Neill; Lucas Radermacher; Tristan Darland (Fishes, 2025)
The ciliary marginal zone (CMZ) is a region in the peripheral-most retina that displays ongoing retinogenesis during growth and expansion of the eye in adulthood. While there is evidence that this capacity also exists in birds and mammals, it is far more robust in fish and amphibians. The process of CMZ retinogenesis is essentially equivalent to that seen early in the central retina; however, its regulation is not fully understood. In a previous study, we attempted to uncover novel regulatory genes by using a forward genetics screen in zebrafish, looking for recessive CMZ mutants. One of the mutants found was called no marginal zone (nmz). The nmz mutant showed relatively normal central retina development, but a lack of cells in the CMZ by 5 days post fertilization (dpf). Mapping, genomic sequencing, and complementation analysis using a second mutant line (m863) isolated in another laboratory showed that a mutation in damage-specific DNA binding protein-1 (ddb-1) gene underlies the phenotype seen in nmz. BrdU labeling suggested that later expansion and differentiation of CMZ retinal progenitors is more affected by ddb-1 loss than the earlier process of stem cell asymmetric division. As was seen for the m863 mutant and in other studies with mice, one profound effect of ddb-1 loss in nmz was the upregulation in expression of tp53 and several of its downstream effectors. Several important genes important in CMZ retinogenesis are also downregulated in the nmz mutant. The change in gene expression would suggest that ddb-1 loss leads to increased cell cycle disruption and apoptosis at the expense of CMZ retinogenesis. While homozygosity is lethal, heterozygous fish appear to be completely normal in morphology, visual function, and behavior.

A novel insertion/deletion in APC promotor 1B is associated with both gastric and colon polyposis - Frankie Fann; Marcy Richardson; Douglas Riegert-Johnson; Colin C. Young; Brittany F. Sears (Familial Cancer, 2025)

The Need for and Challenges of Nutrition and Dietetics Registry Studies Part II: A Primer for the Design and Implementation of Registry Studies in the Academy of Nutrition and Dietetics Health Informatics Infrastructure - Lindsay Woodcock; Casey R. Colin; Erin Lamers-Johnson; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

The geomorphic evolution of the Tasmantid Seamount Chain - Alysha M. Johnson; Mark E. Dickson; Sarah Hamylton; Colin D. Woodroffe (Marine Geology, 2025)

New allometric models for the USA create a shift in forest carbon estimation, modeling, and mapping - Lucas K. Johnson; Michael J. Mahoney; Grant M. Domke; Colin M. Beier (Forest Ecology and Management, 2025)

Declining trends in canopy disturbance across reserve forest landscapes of the northeastern US - Madeleine L. Desrochers; Elizabeth A. Clippard; Lucas K. Johnson; Colin M. Beier (Forest Ecology and Management, 2025)

Faecal contamination determines bacterial assemblages over natural environmental parameters within intermittently opened and closed lagoons (ICOLLs) during high rainfall - Nathan L.R. Williams; Nachshon Siboni; Jaimie Potts; Peter Scanes; Colin Johnson; Melanie James; Vanessa McCann; Nine Le Reun; William L King; Justin R. Seymour (Water Research, 2025)

Embryological incubation temperature modulates behaviour in larval white sturgeon (Acispencer transmontanus) - Trevor J. Hamilton; Katherine Cheung; James Hudson; Joshua Szaszkiewicz; Erica Ingraham; Jeffrey Krook; Andréa Johnson; Brian Franczak; Steve McAdam; Colin J. Brauner (Journal of Thermal Biology, 2025)

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

Electric buses as an air pollution and meteorological observation network: Methodology and preliminary results - Daniel L. Mendoza; Andres Gonzalez; Alexander A. Jacques; Colin M. Johnson; Peter T. Whelan; John D. Horel (Science of The Total Environment, 2024)

Estimating merchantable and non-merchantable wood volume in slash walls using terrestrial and airborne LiDAR - Nicholas Cranmer; Tao Han; Brett Chedzoy; Peter J. Smallidge; Colin Beier; Lucas Johnson; Xiangtao Xu (Forest Ecology and Management, 2024)

Species-specific bioassays reveal spatial variation in chemical contamination of green sea turtles - Dylan White-Kiely; Kimberly A. Finlayson; Colin J. Limpus; Matthew Johnson; Jason P. van de Merwe (Marine Environmental Research, 2024)

Correction: On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Simulation of chloropicrin emissions in response to soil conditions and applicator practices - Colin R. Brown; Atac Tuli; Yvan A. Delgado de la flor; Jazmin G. Johnson; Maziar Kandelous (Science of The Total Environment, 2024)

Thermal tolerance for the tropical clawed frog, Xenopus tropicalis with comments on comparative methods for amphibian studies - Quenton M. Tuckett; Jeffrey E. Hill; Katie Everett; Colin Goodman; Emily S. Wooley; Allison Durland Donahou; Lauren Lapham; Katherine Buckman; Steve Johnson; Christina Romagosa (Journal of Thermal Biology, 2024)

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

Product repair in a circular economy: Exploring public repair behavior from a systems perspective - Keshav Parajuly; James Green; Jessika Richter; Michael Johnson; Jana Rückschloss; Jef Peeters; Ruediger Kuehr; Colin Fitzpatrick (Journal of Industrial Ecology, 2024)
Repair practices are driven not only by consumers’ internal motivation, but also by external infrastructural, social including cultural, financial, and political factors. We explore these factors with the goal of understanding the public repair of electrical and electronic products (e‐products) from a systems perspective to help devise appropriate change interventions. We document (a) behavioral aspects, (b) techno‐economic factors, and (c) intervention strategies aimed at promoting repair practices. To gauge this, a survey was administered among 922 volunteers across 14 countries with experience in repairing e‐products at public repair events. Findings suggest that while behavioral constructs including personal values, beliefs, and attitudes toward product repair are the main proximal drivers of intention to repair, the ability to repair plays an important role. Further, these individual factors are influenced by the techno‐economic settings such as access to repair services, economic benefits, and the ease of product repair stands out as the key enablers for product lifetime extension. As per intervention strategies, the results highlight economic incentives, regulatory requirements, and public awareness as the key drivers. However, influencing repair behavior directly may not always be the most effective strategy. New initiatives to improve involvement should focus on more repairable products, exploiting the innovative potentials of commercial as well as non‐profit repair initiatives, education, and supporting the development of skills among volunteer repairers.

On the Relationship Between Aquatic CO2 Concentration and Ecosystem Fluxes in Some of the World’s Key Wetland Types - Jessica L. Richardson; Ankur R. Desai; Jonathan Thom; Kim Lindgren; Hjalmar Laudon; Matthias Peichl; Mats Nilsson; Audrey Campeau; Järvi Järveoja; Peter Hawman; Deepak R. Mishra; Dontrece Smith; et al. (Wetlands, 2024)

Elemental analysis of vertebrae discerns diadromous movements of threatened non‐marine elasmobranchs - Michael I. Grant; Peter M. Kyne; Julie James; Yi Hu; Sushmita Mukherji; Yolarnie Amepou; Leontine Baje; Andrew Chin; Grant Johnson; Tegan Lee; Brandon Mahan; Christopher Wurster; et al. (Journal of Fish Biology, 2023)
River sharks ( Glyphis spp.) and some sawfishes (Pristidae) inhabit riverine environments, although their long‐term habitat use patterns are poorly known. We investigated the diadromous movements of the northern river shark ( Glyphis garricki ), speartooth shark ( Glyphis glyphis ), narrow sawfish ( Anoxypristis cuspidata ), and largetooth sawfish ( Pristis pristis ) using in situ laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) on vertebrae to recover elemental ratios over each individual's lifetime. We also measured elemental ratios for the bull shark ( Carcharhinus leucas ) and a range of inshore and offshore stenohaline marine species to assist in interpretation of results. Barium (Ba) was found to be an effective indicator of freshwater use, whereas lithium (Li) and strontium (Sr) were effective indicators of marine water use. The relationships between Ba and Li and Ba and Sr were negatively correlated, whereas the relationship between Li and Sr was positively correlated. Both river shark species had elemental signatures indicative of prolonged use of upper‐estuarine environments, whereas adults appear to mainly use lower‐estuarine environments rather than marine environments. Decreases in Li:Ba and Sr:Ba at the end of the prenatal growth zone of P. pristis samples indicated that parturition likely occurs in fresh water. There was limited evidence of prolonged riverine habitat use for A. cuspidata . The results of this study support elemental–environment relationships observed in teleost otoliths and indicate that in situ LA‐ICP‐MS elemental characterization is applicable to a wide range of elasmobranch species as a discriminator for use and movement across salinity gradients. A greater understanding of processes that lead to element incorporation in vertebrae, and relative concentrations in vertebrae with respect to the ambient environment, will improve the applicability of elemental analysis to understand movements across the life history of elasmobranchs into the future.

Identification and quantification of Acanthamoeba spp. within seawater at four coastal lagoons on the east coast of Australia - Binod Rayamajhee; Nathan L.R. Williams; Nachshon Siboni; Kiri Rodgers; Mark Willcox; Fiona L. Henriquez; Justin R. Seymour; Jaimie Potts; Colin Johnson; Peter Scanes; Nicole Carnt (Science of The Total Environment, 2023)

Mapping historical forest biomass for stock-change assessments at parcel to landscape scales - Lucas K. Johnson; Michael J. Mahoney; Madeleine L. Desrochers; Colin M. Beier (Forest Ecology and Management, 2023)

Middle Palaeolithic occupation of the southern North Sea Basin: evidence from the Sandscaping sediments emplaced on the beach between Bacton and Walcott, Norfolk, UK - Rob Davis; Nick Ashton; Rachel Bynoe; John Craven; Rob Ferguson; Ian Gardner; Tim Grimmer; Claire Harris; Marcus Hatch; Colin Johnson; Joanne Leonard; Simon Lewis; et al. (Journal of Quaternary Science, 2023)
During the summer of 2019, the Bacton to Walcott Coastal Management Scheme involved the emplacement on to the foreshore of 1.8 million cubic metres of sand and gravel dredged from the submerged sediments of the Palaeo‐Yare in the southern North Sea 11 km off Great Yarmouth. During the following 2‐year period, an active group of collectors identified Palaeolithic artefacts eroding from these sediments, including Levallois cores and flakes, and cordiform handaxes. In this paper, we present an analysis of the lithic artefacts, and consider the relationships between the different elements of the assemblage. We discuss its significance in the context of the Middle Palaeolithic record of northwest Europe and the light it shines on the human occupation of the submerged landscape of the southern North Sea during the later Middle Pleistocene. Interrogation of beach survey data shows the reworking of these sediments to the southeast towards Happisburgh where archaeologically significant exposures of the Cromer Forest‐bed Formation are located. The implications of the introduction of a Middle Palaeolithic assemblage to this stretch of the North Norfolk Coast are considered, highlighting the importance of continuing dialogue between researchers, local authorities and local communities for capturing information and monitoring this critical Palaeolithic resource.

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Phenological assessment of transpiration: The stem-temp approach for determining start and end of season - Magali F. Nehemy; Zoe Pierrat; Jason Maillet; Andrew D. Richardson; Jochen Stutz; Bruce Johnson; Warren Helgason; Alan G. Barr; Colin P. Laroque; Jeffrey J. McDonnell (Agricultural and Forest Meteorology, 2023)

Classification and mapping of low-statured shrubland cover types in post-agricultural landscapes of the US Northeast - Michael J Mahoney; Lucas K Johnson; Abigail Z Guinan; Colin M Beier (International Journal of Remote Sensing, 2022)

M‐Risk : A framework for assessing global fisheries management efficacy of sharks, rays and chimaeras - C. Samantha Sherman; Glenn Sant; Colin A. Simpfendorfer; Eric D. Digel; Patrick Zubick; Grant Johnson; Michael Usher; Nicholas K. Dulvy (Fish and Fisheries, 2022)
Fisheries management is essential to guarantee sustainable capture of target species and avoid undesirable declines of incidentally captured species. A key challenge is halting and reversing declines of shark and ray species, and specifically assessing the degree to which management is sufficient to avoid declines in relatively data‐poor fisheries. While ecological risk analyses focus on intrinsic ‘productivity’ and extrinsic ‘susceptibility’, one would ideally consider the influence of ‘fisheries management’. Currently, there is no single management evaluation that can be applied to a combination of fishery types at the scale of individual country or Regional Fisheries Management Organizations (RFMOs). Here, we outline a management‐risk (M‐Risk) framework for sharks, rays and chimaeras used to evaluate species' risk of overfishing resulting from ineffective management. We illustrate our approach with application to one country (Ecuador) and RFMO (Inter‐American Tropical Tuna Commission) and illustrate the variation in scores among species. We found that while both management units assessed had similar overall scores, the scores for individual attributes varied. Ecuador scored higher in reporting‐related attributes, while the IATTC scored higher in attributes related to data collection and use. We evaluated whether the management of individual species was sufficient for their relative sensitivity by combining the management‐risk score for each species with their intrinsic sensitivity to determine a final M‐Risk score. This framework can be applied to determine which species face the greatest risk of overfishing and be used by fisheries managers to identify effective management policies by replicating regulations from countries with lower risk scores.

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.

Ground-Truthing Forest Change Detection Algorithms in Working Forests of the US Northeast - Madeleine L Desrochers; Wayne Tripp; Stephen Logan; Eddie Bevilacqua; Lucas Johnson; Colin M Beier (Journal of Forestry, 2022)
The need for reliable landscape-scale monitoring of forest disturbance has grown with increased policy and regulatory attention to promoting the climate benefits of forests. Change detection algorithms based on satellite imagery can address this need but are largely untested for the forest types and disturbance regimes of the US Northeast, including management practices common in northern hardwoods and mixed hardwood-conifer forests. This study ground-truthed the “off-the-shelf” outputs of three satellite-based change detection algorithms using detailed harvest records and maps covering 43,000 ha of working forests in northeastern New York.

A 2019 Outbreak Investigation of Hepatitis A Virus Infections in the United States Linked to Imported Fresh Blackberries - Monica McClure; Johnson Nsubuga; Martha P. Montgomery; Erin Jenkins; Alvin Crosby; Daniela Schoelen; Colin Basler; Sumathi Ramachandran; Yulin Lin; Guo-liang Xia; Yury Khudaykov; Vilasini Suktankar; et al. (Food and Environmental Virology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Warming temperatures could expose more than 1.3 billion new people to Zika virus risk by 2050 - Sadie J. Ryan; Colin J. Carlson; Blanka Tesla; Matthew H. Bonds; Calistus N. Ngonghala; Erin A. Mordecai; Leah R. Johnson; Courtney C. Murdock (Global Change Biology, 2021)
In the aftermath of the 2015 pandemic of Zika virus (ZIKV), concerns over links between climate change and emerging arboviruses have become more pressing. Given the potential that much of the world might remain at risk from the virus, we used a previously established temperature‐dependent transmission model for ZIKV to project climate change impacts on transmission suitability risk by mid‐century (a generation into the future). Based on these model predictions, in the worst‐case scenario, over 1.3 billion new people could face suitable transmission temperatures for ZIKV by 2050. The next generation will face substantially increased ZIKV transmission temperature suitability in North America and Europe, where naïve populations might be particularly vulnerable. Mitigating climate change even to moderate emissions scenarios could significantly reduce global expansion of climates suitable for ZIKV transmission, potentially protecting around 200 million people. Given these suitability risk projections, we suggest an increased priority on research establishing the immune history of vulnerable populations, modeling when and where the next ZIKV outbreak might occur, evaluating the efficacy of conventional and novel intervention measures, and increasing surveillance efforts to prevent further expansion of ZIKV.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Assessing groundwater sustainability under changing climate using isotopic tracers and climate modelling, southwest Ohio, USA - Zelalem K. Bedaso; Shuang-Ye Wu; Amber N. Johnson; Colin McTighe (Hydrological Sciences Journal, 2019)

Rapid thermal adaptation in a marine diatom reveals constraints and trade‐offs - Daniel R. O'Donnell; Carolyn R. Hamman; Evan C. Johnson; Colin T. Kremer; Christopher A. Klausmeier; Elena Litchman (Global Change Biology, 2018)
Rapid evolution in response to environmental change will likely be a driving force determining the distribution of species across the biosphere in coming decades. This is especially true of microorganisms, many of which may evolve in step with warming, including phytoplankton, the diverse photosynthetic microbes forming the foundation of most aquatic food webs. Here we tested the capacity of a globally important, model marine diatom Thalassiosira pseudonana , for rapid evolution in response to temperature. Selection at 16 and 31°C for 350 generations led to significant divergence in several temperature response traits, demonstrating local adaptation and the existence of trade‐offs associated with adaptation to different temperatures. In contrast, competitive ability for nitrogen (commonly limiting in marine systems), measured after 450 generations of temperature selection, did not diverge in a systematic way between temperatures. This study shows how rapid thermal adaptation affects key temperature and nutrient traits and, thus, a population's long‐term physiological, ecological, and biogeographic response to climate change.

Marine Microalgae: Climate, Energy, and Food Security from the Sea - Charles Greene; Mark Huntley; Ian Archibald; Léda Gerber; Deborah Sills; Joe Granados; Jefferson Tester; Colin Beal; Michael Walsh; Robert Bidigare; Susan Brown; William Cochlan; et al. (Oceanography, 2016)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

Marine Microphytobenthic Assemblage Shift along a Natural Shallow-Water CO2 Gradient Subjected to Multiple Environmental Stressors - Vivienne Johnson; Colin Brownlee; Marco Milazzo; Jason Hall-Spencer (Journal of Marine Science and Engineering, 2015)
Predicting the effects of anthropogenic CO2 emissions on coastal ecosystems requires an understanding of the responses of algae, since these are a vital functional component of shallow-water habitats. We investigated microphytobenthic assemblages on rock and sandy habitats along a shallow subtidal pCO2 gradient near volcanic seeps in the Mediterranean Sea. Field studies of natural pCO2 gradients help us understand the likely effects of ocean acidification because entire communities are subjected to a realistic suite of environmental stressors such as over-fishing and coastal pollution. Temperature, total alkalinity, salinity, light levels and sediment properties were similar at our study sites. On sand and on rock, benthic diatom abundance and the photosynthetic standing crop of biofilms increased significantly with increasing pCO2. There were also marked shifts in diatom community composition as pCO2 levels increased. Cyanobacterial abundance was only elevated at extremely high levels of pCO2 (>1400 μatm). This is the first demonstration of the tolerance of natural marine benthic microalgae assemblages to elevated CO2 in an ecosystem subjected to multiple environmental stressors. Our observations indicate that Mediterranean coastal systems will alter as pCO2 levels continue to rise, with increased photosynthetic standing crop and taxonomic shifts in microalgal assemblages.

Prolonged isolation and persistence of a common endemic on granite outcrops in both mesic and semi‐arid environments in south‐western Australia - Sarah‐Louise Tapper; Margaret Byrne; Colin J. Yates; Gunnar Keppel; Stephen D. Hopper; Kimberly Van Niel; Antonius G. T. Schut; Laco Mucina; Grant W. Wardell‐Johnson (Journal of Biogeography, 2014)
Aim Granite outcrops may be able to act as refugia for species during adverse climate change, owing to their topographic complexity. We assessed this hypothesis by examining phylogeographical patterns in a common, geographically widespread granite endemic, Stypandra glauca (Hemerocallidaceae). Location Granite outcrops of the Southwest Australian Floristic Region, Western Australia. Methods Twenty‐four tetraploid individuals of the granite endemic Stypandra glauca were sampled from each of 12 granite outcrops: 7 from a mesic environment and 5 from the semi‐arid region. Phylogenetic reconstruction and divergence‐dating was achieved using Bayesian and parsimony analyses of chloroplast haplotypes from 90 individuals. Nuclear diversity and population differentiation were analysed across all individuals using 10 microsatellite loci. Results Stypandra glauca exhibited high (chloroplast) or moderate (nuclear) levels of divergence among, and low diversity within, outcrops. Haplotype diversity was high in both sampling regions, and each haplotype was unique to one outcrop. There was little correlation between geographical and genetic distance. Both nuclear and chloroplast diversity were higher in southern (mesic) outcrops than in northern (semi‐arid) outcrops, although the level of chloroplast divergence among outcrops was similar for both climatic regions. Main conclusions The levels of divergence and low diversity revealed in S. glauca support a scenario of prolonged isolation and persistence on granite outcrops in both mesic and semi‐arid climatic regions, with no evidence of contraction–expansion dynamics across the outcrop network. The higher levels of diversity in the southern populations may result from the maintenance of a larger effective population size in southern regions, which retained more mesic climates during drier glacial periods. Although the climatic conditions differ between outcrops in this study, our results indicate that outcrops in both regions have harboured S. glauca throughout climatic changes, accentuating the value of these habitats to biodiversity conservation under future changing climate.

Evaluation of Life Cycle Assessment Recycling Allocation Methods - Jeremiah X. Johnson; Colin A. McMillan; Gregory A. Keoleian (Journal of Industrial Ecology, 2013)
Summary Life cycle assessment practitioners struggle to accurately allocate environmental burdens of metals recycling, including the temporal dimension of environmental impacts. We analyze four approaches for calculating aluminum greenhouse gas emissions: the recycled content (RC) or cut‐off approach, which assumes that demand for recycled content displaces primary production; end‐of‐life recycling (EOLR), which assumes that postuse recycling displaces primary production; market‐based (MB) approaches, which estimate changes in supply and demand using price elasticities; and value‐corrected substitution (VCS), which allocates impact based on price differences between primary and recycled material. Our analysis suggests that applications of the VCS approach do not adequately account for the changing scrap to virgin material price ratio over time, whereas MB approaches do not address stock accumulation and depletion. The EOLR and RC approaches were analyzed using two case studies: U.S. aluminum beverage cans and vehicle engine blocks. These approaches produced similar results for beverage cans, which have a closed material loop system and a short product life. With longer product lifetimes, as noted with the engine blocks, the magnitude and timing of the emissions differs greatly between the RC and EOLR approaches. The EOLR approach indicates increased impacts at the time of production, offset by negative impacts in future years, whereas the RC approach assumes benefits to increased recycled content at the time of production. For vehicle engine blocks, emissions using EOLR are 140% higher than with RC. Results are highly sensitive to recycled content and future recycling rates, and the choice of allocation methods can have significant implications for life cycle studies.

Temperate and tropical brown macroalgae thrive, despite decalcification, along natural CO 2 gradients - Vivienne R. Johnson; Bayden D. Russell; Katharina E. Fabricius; Colin Brownlee; Jason M. Hall‐Spencer (Global Change Biology, 2012)
Predicting the impacts of ocean acidification on coastal ecosystems requires an understanding of the effects on macroalgae and their grazers, as these underpin the ecology of rocky shores. Whilst calcified coralline algae (Rhodophyta) appear to be especially vulnerable to ocean acidification, there is a lack of information concerning calcified brown algae (Phaeophyta), which are not obligate calcifiers but are still important producers of calcium carbonate and organic matter in shallow coastal waters. Here, we compare ecological shifts in subtidal rocky shore systems along CO 2 gradients created by volcanic seeps in the Mediterranean and Papua New Guinea, focussing on abundant macroalgae and grazing sea urchins. In both the temperate and tropical systems the abundances of grazing sea urchins declined dramatically along CO 2 gradients. Temperate and tropical species of the calcifying macroalgal genus Padina (Dictyoaceae, Phaeophyta) showed reductions in Ca CO 3 content with CO 2 enrichment. In contrast to other studies of calcified macroalgae, however, we observed an increase in the abundance of Padina spp. in acidified conditions. Reduced sea urchin grazing pressure and significant increases in photosynthetic rates may explain the unexpected success of decalcified Padina spp. at elevated levels of CO 2 . This is the first study to provide a comparison of ecological changes along CO 2 gradients between temperate and tropical rocky shores. The similarities we found in the responses of Padina spp. and sea urchin abundance at several vent systems increases confidence in predictions of the ecological impacts of ocean acidification over a large geographical range .

Refugia: identifying and understanding safe havens for biodiversity under climate change - Gunnar Keppel; Kimberly P. Van Niel; Grant W. Wardell‐Johnson; Colin J. Yates; Margaret Byrne; Ladislav Mucina; Antonius G. T. Schut; Stephen D. Hopper; Steven E. Franklin (Global Ecology and Biogeography, 2012)
Aim Identifying and protecting refugia is a priority for conservation under projected anthropogenic climate change, because of their demonstrated ability to facilitate the survival of biota under adverse conditions. Refugia are habitats that components of biodiversity retreat to, persist in and can potentially expand from under changing environmental conditions. However, the study and discussion of refugia has often been ad hoc and descriptive in nature. We therefore: (1) provide a habitat‐based concept of refugia, and (2) evaluate methods for the identification of refugia. Location Global. Methods We present a simple conceptual framework for refugia and examine the factors that describe them. We then demonstrate how different disciplines are contributing to our understanding of refugia, and the tools that they provide for identifying and quantifying refugia. Results Current understanding of refugia is largely based on Quaternary phylogeographic studies on organisms in North America and Europe during significant temperature fluctuations. This has resulted in gaps in our understanding of refugia, particularly when attempting to apply current theory to forecast anthropogenic climate change. Refugia are environmental habitats with space and time dimensions that operate on evolutionary time‐scales and have facilitated the survival of biota under changing environmental conditions for millennia. Therefore, they offer the best chances for survival under climate change for many taxa, making their identification important for conservation under anthropogenic climate change. Several methods from various disciplines provide viable options for achieving this goal. Main conclusions The framework developed for refugia allows the identification and description of refugia in any environment. Various methods provide important contributions but each is limited in scope; urging a more integrated approach to identify, define and conserve refugia. Such an approach will facilitate better understanding of refugia and their capacity to act as safe havens under projected anthropogenic climate change.

Patch depletion behavior differs between sympatric folivorous primates - Kaia J. Tombak; Andrea J. Reid; Colin A. Chapman; Jessica M. Rothman; Caley A. Johnson; Rafael Reyna-Hurtado (Primates, 2012)

Facilitating adaptation of biodiversity to climate change: a conceptual framework applied to the world’s largest Mediterranean-climate woodland - Suzanne M. Prober; Kevin R. Thiele; Philip W. Rundel; Colin J. Yates; Sandra L. Berry; Margaret Byrne; Les Christidis; Carl R. Gosper; Pauline F. Grierson; Kristina Lemson; Tom Lyons; Craig Macfarlane; et al. (Climatic Change, 2012)

Severity of drinking as a predictor of efficacy of the combination of ondansetron and topiramate in rat models of ethanol consumption and relapse - Wendy J. Lynch; Colin Bond; Florence J. Breslin; Bankole A. Johnson (Psychopharmacology, 2011)

Molecular Genetics and Pathogenic Mechanisms for the Severe Ciliopathies: Insights into Neurodevelopment and Pathogenesis of Neural Tube Defects - Clare V. Logan; Zakia Abdel-Hamed; Colin A. Johnson (Molecular Neurobiology, 2011)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

Evaluation of the Viability of Pathogenic Filamentous Fungi after Prolonged Storage in Sterile Water and Review of Recent Published Studies on Storage Methods - Andrew M. Borman; Adrien Szekely; Colin K. Campbell; Elizabeth M. Johnson (Mycopathologia, 2006)

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

A novel locus for Meckel-Gruber syndrome, MKS3 , maps to chromosome 8q24 - Neil Morgan; Paul Gissen; Saghira Sharif; Laura Baumber; Joan Sutherland; Deirdre Kelly; Kingi Aminu; Christopher Bennett; Geoffrey Woods; Robert Mueller; Richard Trembath; Eamonn Maher; et al. (Human Genetics, 2002)

The Global Exposure of Forests to Air Pollutants - David Fowler; J. Neil Cape; Mhairi Coyle; Chris Flechard; Johan Kuylenstierna; Kevin Hicks; Dick Derwent; Colin Johnson; David Stevenson (Water, Air, & Soil Pollution, 1999)

Electron-energy-loss spectroscopic imaging of calcium and nitrogen in the cell walls of apple fruits - I. Max Huxham; Michael C. Jarvis; Lynette Shakespeare; Colin J. Dover; David Johnson; J. Paul Knox; Graham B. Seymour (Planta, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

CHARACTERIZATION OF POLYMORPHIC TRINUCLEOTIDE MICROSATILLITE LOCI IN THE GREAT‐TAILED GRACKLE - Colin. R. Hughes; Ryan. Kavlie; Kristine. Johnson (Molecular Ecology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)